Global Driving of Auroral Precipitation: 1. Balance of Sources. Issue 7 (11th July 2022) - Mukhopadhyay, Agnit; Welling, Daniel; Liemohn, Michael; Ridley, Aaron; Burleigh, Meghan; Wu, Chen; Zou, Shasha; Connor, Hyunju; Vandegriff, Elizabeth; Dredger, Pauline; Tóth, Gabor
Abstract: The accurate determination of auroral precipitation in global models has remained a daunting and rather inexplicable obstacle. Understanding the calculation and balance of multiple sources that constitute the aurora, and their eventual conversion into ionospheric electrical conductance, is critical for improved prediction of space weather events. In this study, we present a semi‐physical global modeling approach that characterizes contributions by four types of precipitation—monoenergetic, broadband, electron, and ion diffuse—to ionospheric electrodynamics. The model uses a combination of adiabatic kinetic theory and loss parameters derived from historical energy flux patterns to estimate auroral precipitation from magnetohydrodynamic (MHD) quantities. It then converts them into ionospheric conductance that is used to compute the ionospheric feedback to the magnetosphere. The model has been employed to simulate the 5–7 April 2010 Galaxy15 space weather event. Comparison of auroral fluxes show good agreement with observational data sets like NOAA‐DMSP and OVATION Prime. The study shows a dominant contribution by electron diffuse precipitation, accounting for ∼74% of the auroral energy flux. However, contributions by monoenergetic and broadband sources dominate during times of active upstream solar conditions, providing for up to 61% of the total hemispheric power. The study also finds a greater role played by broadband precipitation in ionospheric electrodynamics which accounts for ∼31% of the Pedersen conductance. Plain Language Summary: The aurora is comprised of electrically charged particles that enter the upper atmosphere from outer space. The entry is driven by diverse processes at different locations of the high‐latitude atmosphere; these helps define the different sources that constitute the bulk of the aurora. Since the aurora is an important phenomenon in the study of near‐Earth space physics and space weather, it is important to account for the contribution and balance of each individual source and deduce their impact. In this study, we have introduced a novel modeling approach that is capable of estimating contributions from four diverse sources of aurora, and used this approach to study auroral dynamics during a famous space weather event. Our results indicate that the proportion and strength of each source varies over time, location, and activity. Additionally, we identify which sources have a pronounced contribution to the ionosphere's electrical conductance. Key Points: A semi‐physical global modeling approach is used to estimate diffuse and discrete sources of auroral precipitation during the Galaxy15 event Diffuse sources contribute 74% of the total auroral power. Discrete sources are strongly driven by activity and can contribute up to 61% Broadband precipitation contributes 31% of the auroral Pedersen conductance playing a significant role in ionospheric electrodynamics